2018
DOI: 10.1371/journal.pone.0199157
|View full text |Cite
|
Sign up to set email alerts
|

Classification of primary angle closure spectrum with hierarchical cluster analysis

Abstract: PurposeTo classify subjects with primary angle closure into clusters based on features from anterior segment optical coherence tomography (ASOCT) imaging and to explore how these clusters correspond to disease subtypes, including primary angle closure suspect (PACS), primary angle closure glaucoma(PACG), acute primary angle closure (APAC) and fellow eyes of APAC and reveal the factors that become more predominant in each subtype of angle closure.MethodA cross-sectional study of 248 eyes of 198 subjects(88 PACS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 31 publications
1
22
0
4
Order By: Relevance
“…40 Cluster 1 had the smallest ACD and ACA, as well as the largest LV, suggesting a pushing mechanism as a result of the forward movement of the lens and increased LT. 40 Cluster 2 had the largest IT at 2000 μ, largest IA, and deepest ACD, which may result in angle crowding and subsequent angle closure due to a predominant iris component. 40 Cluster 3 was characterized by elements of both clusters 1 and 2 and a higher iris curvature suggesting a predominant PB mechanism. 40 We further categorized the enrolled 405 PACS eyes into different subgroups based on the main angle closure mechanisms.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…40 Cluster 1 had the smallest ACD and ACA, as well as the largest LV, suggesting a pushing mechanism as a result of the forward movement of the lens and increased LT. 40 Cluster 2 had the largest IT at 2000 μ, largest IA, and deepest ACD, which may result in angle crowding and subsequent angle closure due to a predominant iris component. 40 Cluster 3 was characterized by elements of both clusters 1 and 2 and a higher iris curvature suggesting a predominant PB mechanism. 40 We further categorized the enrolled 405 PACS eyes into different subgroups based on the main angle closure mechanisms.…”
Section: Discussionmentioning
confidence: 96%
“…Moghimi et al also reported three different angle closure subtypes among PACS, PACG, acute primary angle closure, and the fellow eyes of acute primary angle closure using statistical clustering analysis based on ASOCT parameters. 40 Cluster 1 had the smallest ACD and ACA, as well as the largest LV, suggesting a pushing mechanism as a result of the forward movement of the lens and increased LT. 40 Cluster 2 had the largest IT at 2000 µ, largest IA, and deepest ACD, which may result in angle crowding and subsequent angle closure due to a predominant iris component. 40 Cluster 3 was characterized by elements of both clusters 1 and 2 and a higher iris curvature suggesting a predominant PB mechanism.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Patients with APAC had to satisfy all four of the following criteria to be included in the study. (a) at least two of the symptoms of an acute IOP elevation: ocular or peri-ocular pain, nausea and/or vomiting, halos; (b) clinical signs: conjunctival injection, microcytic corneal edema, mid-dilated pupil, and shallow AC; (c) IOP at presentation of at least 30 mmHg; (d) presence of occludable angle, confirmed by gonioscopy [17]. Occludable angle closure was defined if the posterior trabecular meshwork (TM) could not be visualized in at least 3 quadrants.…”
Section: Methodsmentioning
confidence: 99%